(untitled) (Biological Sciences - PJSIR, 1998)
Kenaf (Hibiscus sabdariffa] was subjected to acetosolv pulping catalyzed by hydrochloric acid. The effect of various operational conditions like percent acid, percent catalyst and solid-liquor ratio on the percent yield and the quality of the resultant fractionated product was studied. Extensivedelignification was achieved under avariety ofoperational conditions, leading to solid residues with lignin contents of less than 5%. The kinetics of the delignification process was also studied. The optimum pulping conditions established for this raw material were 95% acid, 0.25% catalyst and solid-liquor ratio of I: 12.5 in time of 120 rnins giving a fractionated. product having yield and a-cellulose contents of 54.5 and 85.7% respectively. Further, its fiber dimensions were found tobe comparable to that of certain woods with mean fiber length and diameter of 1.506 and 0.0295 mm, respectively.